Africa : altered states, ordinary miracles - Dowden, Richard (Public Affairs, 2009)
In captivating prose, Dowden spins tales of cults and commerce in Senegal and traditional spirituality in Sierra Leone; analyzes the impact of oil and the Internet on Nigeria and aid on Sudan; and examines what has gone so badly wrong in Rwanda and the Congo.